Surgical management of squamous cell vulvar cancer without clitoris, urethra or anus involvement - Alpaslan Kaban; Işık Kaban; Selim Afşar (Elsevier, 2017)
Vulvar cancers, which constitute 5% of all gynecologic cancers, are the fourth most common female genital cancers, preceded by uterine, ovarian and cervical cancers. The treatment methods employed for vulvar cancers have changed over the years, with previously applied radical surgical approaches, such as en bloc resection, being gradually suspended in favor of treatment approaches that require dissection of less tissue. While the removal of less tissue, which today's approaches have focused on, prevents morbidity, this method seems to result in higher risks of recurrence. It is therefore important that the balance between preventing the recurrence of the disease and forefending against postoperative complications and vulvar deformity be properly understood. As a working assumption, if patients with vulvar cancer are diagnosed at an early stage, properly evaluated and administered appropriate treatment, the most positive results can be obtained. This paper aims to highlight this assumption and demonstrate, through the provision of actual data, how to plan the treatment approach for patients who are diagnosed early. Statements extracted from the National Comprehensive Cancer Network (NCCN) Guidelines Version 1.2016 Sub-Committees on vulvar squamous cell carcinoma and articles by the European Society of Gynaecological Oncology (ESGO) regarding Vulvar Cancer Recommendations were used to obtain updated information.